Impacts of outsourcing on wage: New evidence for the Brazilian debate - André Gambier Campos (Institute for Applied Economic Research (ipea), 2016)
This article brings empirical evidence for outsourcing debate in Brazil. This evidence is the result of a new methodology, which uses new microdata, recently released by the Ministry of Labour. With this methodology, it is possible to gather information about: i) 3,10 million employees with medium likelihood of being outsourced; ii) 0,92 million employees with high likelihood of being outsourced. And, when comparing wages of direct and outsourced employees, it is possible to notice that outsourced (with high likelihood) face a decrease in their wages, in most of the situations examined.
Keywords: J31; J38; J80; 330; outsourcing; employment; wage; regulation; State